Detection of DNA Double Strand Breaks by γH2AX Does Not Result in 53bp1 Recruitment in Mouse Retinal Tissues - Müller, Brigitte; Ellinwood, N. M.; Lorenz, Birgit; Stieger, Knut (Frontiers in Neuroscience, 2018)
Gene editing is an attractive potential treatment of inherited retinopathies. However, it often relies on endogenous DNA repair. Retinal DNA repair is incompletely characterized in humans and animal models. We investigated recruitment of the double stranded break (DSB) repair complex of γH2AX and 53bp1 in both developing and mature mouse neuroretinas. We evaluated the immunofluorescent retinal expression of these proteins during development (P07-P30) in normal and retinal degeneration models, as well as in potassium bromate induced DSB repair in normal adult (3 months) retinal explants. The two murine retinopathy models used had different mutations in Pde6b: the severe rd1 and the milder rd10 models. Compared to normal adult retina, we found increased numbers of γH2AX positive foci in all retinal neurons of the developing retina in both model and control retinas, as well as in wild type untreated retinal explant cultures. In contrast, the 53Bp1 staining of the retina differed both in amount and character between cell types at all ages and in all model systems. There was strong pan-nuclear staining in ganglion, amacrine, and horizontal cells, and cone photoreceptors, which was attenuated. Rod photoreceptors did not stain unequivocally. In all samples, 53Bp1 stained foci only rarely occurred. There was negligible cCo-localization of 53Bp1 and γH2AX staining was a very rare event (< 1% of γH2AX foci in the ONL and < 3% in the INL), suggesting the potential for alternate DSB sensing and repair proteins in the murine retina. At a minimum, murine retinal DSB repair does not appear to follow canonical pathways, and our findings suggests further investigation is warranted.